Developing Indonesia’s palm sugar industry for the ASEAN market: A SWOT–AHP–Maslahah and digital Islamic economy framework - Fahrika, Andi Ika; Buhasyim, Muhammad Abdi; Kadir, Syahruddin (Journal of Islamic Economics Lariba, 2026)
IntroductionIndonesia’s palm sugar industry has considerable potential to support export growth, strengthen the creative economy, and expand the country’s participation in the Association of Southeast Asian Nations market. However, palm sugar producers continue to face limited production capacity, low technological adoption, inadequate promotion, weak quality standardization, insufficient capital, and incomplete business formalization. These constraints require a development strategy that improves competitiveness while creating public welfare in accordance with Islamic economic principles.ObjectivesThis study evaluates strategic alternatives for developing Indonesia’s palm sugar industry in the Association of Southeast Asian Nations market. It also develops an integrated Strengths, Weaknesses, Opportunities, and Threats–Analytic Hierarchy Process–Maslahah framework to assess strategic priorities based on competitiveness and the objectives of Maqasid al-Shariah.MethodThe study employed a quantitative approach using primary data collected through structured questionnaires. Five palm sugar companies in Bone Regency, South Sulawesi, were selected through purposive sampling. Internal and external strategic factors were evaluated through Strengths, Weaknesses, Opportunities, and Threats analysis. The Analytic Hierarchy Process was used to assign weights to the dimensions of Maqasid al-Shariah, while the Maslahah Scorecard assessed each strategy’s contribution to protecting religion, life, intellect, lineage, and wealth.ResultsThe findings show that weaknesses outweighed strengths, while opportunities exceeded external threats. The strategic position was located in Quadrant Three, indicating the need for a turnaround strategy that uses market opportunities to address internal limitations. The total Maslahah score was 3.01, representing a moderate contribution to public welfare. Halal certification, Sharia-compliant business practices, digital innovation, and halal e-commerce received relatively strong assessments. Business continuity, financing access, technological capability, export income, and industry regeneration require further improvement.ImplicationsPolicymakers and industry practitioners should prioritize e-commerce training, halal certification assistance, business registration, quality improvement, Islamic financing, and access to regional export and distribution networks.Originality/NoveltyThis study introduces an integrated strategic framework that evaluates palm sugar development through both commercial competitiveness and Shariah-oriented welfare, connecting digital Islamic economy instruments with sustainable development in the Association of Southeast Asian Nations market.